Dampak Jumlah Kendaraan Besar terhadap Kemacetan Lalu Lintas di Jalan Tol - Nugroho, Leonard Ardian; Latifa, Eva Azhra; Maulani, Eka Olivia (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
The construction and development of road infrastructure, especially toll roads in Indonesia, is often a national strategic project. The purpose of toll roads is to reduce congestion on main roads, and improve the distribution of goods and services. However, congestion also occurs on toll roads, one of which is caused by large low-speed vehicles as a mode for the distribution of goods and services. This study aims to analyse the impact of large vehicles on road performance on the Jakarta-Tangerang toll road. Congestion is expressed in degrees of saturation. Vehicle volume and average vehicle speed as secondary data in this study. Calculations using PKJI 2023 on Freeway. The data was analyzed using Microsoft Excel application and tested regression with SPSS application.  Based on the analysis results, the degree of saturation increases as the number of vehicles increases, so that the average vehicle speed decreases. The degree of saturation calculated on the volume of vehicles of all classes has a significant influence on the vehicles average speed that have the potential to cause congestion by 87% and the remaining 12% is influenced by other factors.